2015
DOI: 10.1124/jpet.115.227850
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Phosphodiesterase 5 Inhibition Enhances Myocardial Protection by Inhaled Nitric Oxide in Ischemia-Reperfusion Injury

Abstract: Enhanced cyclic guanosine monophosphate (cGMP) signaling may attenuate myocardial ischemia-reperfusion injury (I/R) and improve left ventricular (LV) functional recovery after myocardial infarction (MI). We investigated the cardioprotection afforded by inhaled NO (iNO), the phosphodiesterase 5 (PDE5)-specific inhibitor tadalafil (TAD), or their combination (iNO1TAD) in C57Bl6J mice subjected to 6-minute left anterior descending artery ligation followed by reperfusion. We measured plasma and cardiac concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
1
16
0
2
Order By: Relevance
“…Therefore, such combined therapies may represent promising strategies for translational research to improve the outcome of I/R‐injury in patients (Lux et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, such combined therapies may represent promising strategies for translational research to improve the outcome of I/R‐injury in patients (Lux et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The associated increase in cGMP-signaling after the combined treatment suggests the importance of this pathway for beneficial long term structural and functional myocardium remodeling. Therefore, such combined therapies may represent promising strategies for translational research to improve the outcome of I/R-injury in patients (Lux et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, the acute effect of tadalafil as a reno protective agent was demonstrated in experimental renal ischemia/reperfusion injury model in the rat. 17 More recently, Wang et al demonstrated that tadalafil is effective and safe for the treatment of diabetic neuropathy as it increases regional blood flow in the sciatic nerve tissue and improves peripheral nerve function in type II diabetic mice. 18 In the present study, chronic low dose tadalafil treatment attenuated the progression of DN in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In this brief review, we will focus on pharmacological aspects of the cGMP–PKG pathway with updates from recent preclinical and clinical studies in relation to its direct effect on the heart. We also refer readers to excellent recent reviews providing in-depth overview of NO–cGMP–PKG pathway such as [ 40 ].…”
Section: Introductionmentioning
confidence: 99%